THE IDEAS AND IDEALS OF THE XIX CENTURY IN PRILEP AND THE PRILEP REGION - Tocinovski, Vasil (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
The paper presents a review of the book “Prilep and the Prilep region in the ХIХ century (cultural and historical processes)” by the author Slavcho Koviloski. The book was published by “Sovremenost” in Skopje in 2017. For this monograph Koviloski received the prestigious Goce Delchev state award this year. The structure of the book consists of eight chapters in which in a chronologically pedantic and decisive manner Koviloski writes about significant phenomena, processes and manifestations, authors and works that have left permanent traces and results for Prilep and the Prilep region.